Primary Gallbladder Adenocarcinoma in a Cat - Diogenes, Taiani Torquato; Rocha, Mariana Araújo; Sampaio, Keytyanne Oliveira; Olinda, Roberio Gomes; Nunes Pinheiro, Diana Celia Sousa; Sousa Filho, Reginaldo Pereira (Acta Scientiae Veterinariae, 2020)
Background: Biliary tumors have low incidence in cats and are more common in elderly animals. Hepatobiliary tumors have different classifications and their etiology is difficult to interpret. In most cases, the diagnosis is only possible in advanced stages, which clouds the precursor factors. The late diagnosis is explained by the absence or specificity of clinical manifestations and laboratory changes. The majority of hepatobiliary neoplasms in cats are incidental findings in surgeries or necropsies. This study aimed to report clinical, laboratory, pathological and immunohistochemical results in a feline case of gall bladder adenocarcinoma. Case: A cat, male, neutered, mixed breed, 4 years, was admitted at a veterinary clinic with a history of polyuria / polydipsia, anorexia, apathy, jaundice and emesis for 60 days. The animal had been treated in another clinic with silymarin, famotidine and cyanocobalamin, and fed by esophageal tube based on the presumptive clinical diagnosis of cholangitis. The clinical examination revealed jaundice, abdominal pain, weight loss, enlargement of the liver and gallbladder and the presence of a structure in the epigastric region. Based on clinical signs, blood tests (complete blood count and liver enzymes), abdominal ultrasound and thoracic radiography were requested. In the exam results, eosinophilia, bilirubinemia and increased alkaline phosphatase, glutamic pyruvic transaminase and gamma glutamyl transferase were observed, in addition to the presence of icteric and hemolyzed serum. Ultrasound exam revealed thickened and dilated cystic and common ducts, large and thick gallbladder, bile with bile mud, hypoechogenic liver, thickening in the duodenal papilla and enlarged pancreatic and duodenal lymph nodes. There were no alterations in thoracic radiography. Based on the findings, the diagnosis of extrahepatic biliary obstruction was suggested. In celiotomy, dilated gallbladder with a thick blackened wall was observed. Bile puncture was performed for analysis, and total cholecystectomy and removal of obstructive content was performed. The patient suffered cardiorespiratory arrest after the procedure. A fragment of gallbladder and liver were sent to evaluation with histopathology and immunohistochemistry, and results were compatible with gallbladder adenocarcinoma. Discussion: Hepatobiliary neoplasms in cats are uncommon, apart from lymphoma. The incidence is higher in elderly cats and in males, which did not match the animal in this case. The clinical presentation of the condition is quite nonspecific, corroborating with other reports, in which changes are often only evident in advanced stages of the disease. Laboratory and imaging findings pointed to a biliary tree disorder, and cholangitis was suggested. However, the lack of clinical improvement and examination findings of exams lead to an exploratory laparotomy for better inspection of the organs and identification of possible causes. One of the differential diagnoses that should be considered in cats with extrahepatic biliary obstruction is gallbladder adenocarcinoma, especially in animals with an unsatisfactory response in clinical treatment. Tests such as histopathology and immunohistochemistry are essential for the definitive diagnosis of this neoplasm. Surgical resection is indicated in cases of malignant masses, providing longevity and better quality of life. Hypotension is a common complication in hepatobiliary surgeries, which can result in death.